2001
DOI: 10.1002/jat.747
|View full text |Cite
|
Sign up to set email alerts
|

Possible androgenic/anti‐androgenic activity of the insecticide fenitrothion

Abstract: To date, within the field of endocrine disruption, much focus has been placed on chemicals that mimic oestrogens (so-called xenoestrogens), and the number of such chemicals apparently detected continues to grow steadily. Less effort has been expended on investigating chemicals that mimic, or antagonize, other hormones. Nevertheless, a number of chemicals have been reported to have a weak affinity for the androgen receptor, all of which have, to date, been found to have anti-androgenic activity in vivo. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 29 publications
(27 reference statements)
1
24
0
Order By: Relevance
“…28,29) Furthermore, Sohoni et al have determined by hAR-yeast assay that parathion and fenitrothion possess androgenic and anti-androgenic activity and fenitrothion inhibits the stimulatory effect of testosterone propionate on Cowper's gland in the rat. 30) It was found that nitrophenols isolated from DEP possessed not only vasodilatory activity but also estrogenic and anti-androgenic activity. Furthermore, our results suggest that, as a result of diesel exhaust emission or the degradation of various pesticides, the accumulation of nitrophenols (including PNP and PNMC) in the air and soil could have serious deleterious effects on wildlife and human health though disturbance of endocrine and cardiovascular functions.…”
Section: Resultsmentioning
confidence: 99%
“…28,29) Furthermore, Sohoni et al have determined by hAR-yeast assay that parathion and fenitrothion possess androgenic and anti-androgenic activity and fenitrothion inhibits the stimulatory effect of testosterone propionate on Cowper's gland in the rat. 30) It was found that nitrophenols isolated from DEP possessed not only vasodilatory activity but also estrogenic and anti-androgenic activity. Furthermore, our results suggest that, as a result of diesel exhaust emission or the degradation of various pesticides, the accumulation of nitrophenols (including PNP and PNMC) in the air and soil could have serious deleterious effects on wildlife and human health though disturbance of endocrine and cardiovascular functions.…”
Section: Resultsmentioning
confidence: 99%
“…Antiandrogenic compounds so far reported include vinclozolin, linuron, iprodione, chlozolinate, procymidone, flutamide, p,p´-DDE, and ketoconazole (Gray et al 1999a(Gray et al , 1999bLambright et al 2000;McIntyre et al 2000;Ostby et al 1999;You et al 1999). In contrast, both positive and negative results on the antiandrogenic activity of fenitrothion, a relative of fenthion, have been reported (Ashby and Lefevre 2000;Curtis 2001;Sohoni et al 2001;Sunami et al 2000;Tamura et al 2001). The significant antiandrogenic activity of fenitrothion found in our study supports previous findings that fenitrothion has antiandrogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…These situations provide the p o t e n t i a l f o r e n v i r o n m e n t a l e x p o s u r e t o permethrin and its attendant human health risks. Many pesticides have been reported to possess estrogenic or androgenic activities [15][16][17][18][19][20][21][22], and thus are classified as endocrine disruptors. However, relatively few studies have reported on the estrogenic and androgenic activities of permethrin [3,[23][24][25][26], and the results of the studies are in some respects contradictory.…”
mentioning
confidence: 99%